2021
DOI: 10.1021/acs.jctc.0c01338
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Side-Chain NMR Relaxation Data Using Molecular Simulations

Abstract: Proteins display a wealth of dynamical motions that can be probed using both experiments and simulations. We present an approach to integrate side-chain NMR relaxation measurements with molecular dynamics simulations to study the structure and dynamics of these motions. The approach, which we term ABSURDer (average block selection using relaxation data with entropy restraints), can be used to find a set of trajectories that are in agreement with relaxation measurements. We apply the method to deuterium relaxat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 82 publications
0
43
0
Order By: Relevance
“…Moreover, it is assumed that the transition events are infinitely fast, that is, the system can always be found in one particular conformation. This model can be used to study side-chain motions which can undergo fast rotamer transitions, as revealed by MD simulations [24,26,37,49].…”
Section: Rotamer Jumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is assumed that the transition events are infinitely fast, that is, the system can always be found in one particular conformation. This model can be used to study side-chain motions which can undergo fast rotamer transitions, as revealed by MD simulations [24,26,37,49].…”
Section: Rotamer Jumpsmentioning
confidence: 99%
“…Both have lead to a large number of succesfull studies of protein dynamics by NMR [15][16][17][18][19][20]. However, MF or EMF approaches are uninformative on the nature of motions of protein backbone and side-chains, and relaxation analysis has to be complemented with Molecular Dynamics (MD) simulations [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of background intensity and scaling factor is a major step forward with respect to the previous approaches, in which only the weights were determined, because these parameters depend on many features of the system studied (e.g., the solvation shell) and on experimental conditions. Also, very recently, an ensemblereweighting method by using side-chain NMR-relaxation, termed Average Block Selection Using Relaxation Data with Entropy Restraint (ABSURDer), an extension of the ABSURD method of Blackledge and others (Salvi et al, 2016), has been developed by the Lindorff-Larsen group (Kümmerer et al, 2021). This approach takes into account system dynamics, thus enabling us to find the ensemble of trajectories, not just static conformations, consistent with experiment.…”
Section: Reweighting the Conformational Ensemblesmentioning
confidence: 99%
“…However, for certain types of biophysical experiments, time-dependent dynamics must be taken into account. For example, NMR relaxation experiments report on molecular motions which can only be calculated from a time-series of structures or models of the dynamics, such as the Lipari-Szabo model-free approach (Lipari and Szabo, 1982;Brüschweiler et al, 1992;Peter et al, 2001;Salvi et al, 2016;Smith et al, 2020;Kümmerer et al, 2021). Additionally, many biological processes do not happen at equilibrium, but rather involve transitions from one state to another.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For example, time-resolved SAXS and NMR experiments can be used to measure kinetic processes such as conformational changes and binding (Rennella and Brutscher, 2013;Tuukkanen et al, 2017;Cho et al, 2021). While approaches have already been developed to interpret NMR relaxation data using conformational ensembles (Salvi et al, 2016;Kümmerer et al, 2021), future research could involve the development of methods exploiting time-resolved data to resolve biologically relevant transitions.…”
Section: Future Perspectivesmentioning
confidence: 99%